Adaptive modulation technology in LTE-Advanced system - Hongguang DUAN; Li HU; Mei TIAN (Dianxin kexue)
Adaptive modulation technology is an important research content of AMC technology in LTE-Advanced system.The β value of new MCS levels were studied,in which the higher order modulation 256QAM was used,then the general β value of new MCS levels by the iterative algorithm in several different channel models were obtained,according to the convexity of the mean square error function,and compared with the traditional MCS levels.The simulation results show that the new MCS levels provide higher system performance when SNR is high,and the optimized β value makes CQI calculation more accurately.